INFLUENCE OF REGIONAL ORIGINAL REVENUE AND BALANCING FUNDS ON THE FINANCIAL PERFORMANCE OF THE REGIONAL GOVERNMENT OF JOMBANG DISTRICT - Anggraini, Ullif Athiyah; Widajantie, Tituk Diah (International Journal of Economy, Education and Entrepreneurship (IJE3), 2024)
Regional government financial performance measures regional independence in managing potential sources of regional original income (PAD) as the primary value for financing regional expenditure so that it does not depend on central government balancing funds. This research aims to test and determine the influence of (PAD) and balancing funds on the financial performance of the Jombang Regency regional government. Quantitative methods are used in this type of research. The sample for this research is five years from the Jombang Regency regional government budget realization report for 2018-2022. The non-probability sampling method was used in this research, and saturated sampling techniques were utilized. The classical assumption test, multiple linear regression analysis, and hypothesis testing were used as data analysis using SPSS 26 tools. The results of this research were that PAD and balancing funds had a positive and significant effect on the financial performance of the Jombang Regency regional government